The state of adolescent immunization in Nigeria: A wake up call for all stakeholders (2019)
The number of children who survive to adolescence is increasing in Nigeria, significantly due to the success of child survival programs, with immunization as a major theme. However, the national immunization schedule in Nigeria is presently restricted to early childhood with no attention paid to immunization in adolescence. Presently, the vaccines that are readily available for adolescents include tetanus toxoid which is normally administered to pregnant women, so necessarily includes adolescent mothers; and a few research programs which offers hepatitis B vaccines. Also, there are few Nigerian adolescents who access immunization as a requirement for travelling outside the country or as a result of parental effort. Knowledge and awareness about adolescent immunization is generally poor. Nigerian adolescents have been shown to be poorly protected from tetanus, rubella and hepatitis B which are vaccine preventable. Neonatal, childhood and adult tetanus, congenital rubella syndrome, cervical cancer and hepatocellular carcinoma are just few of the diseases whose incidence can be reduced with an effective adolescent immunization program. This will also ensure that the gain of childhood immunization is concretized and socio-economic losses as a result of vaccine preventable diseases are eliminated to create a healthy and vibrant workforce. There is an urgent need to build a viable adolescent immunization program in Nigeria as adolescents represent a window of opportunity to prevent diseases which affect both the younger and older age group. This can be extended to other developing countries as well.